Synergistic optimization of thermoelectric properties in Ca(Yb)Mg2Bi2 composited SnTe based alloy. (November 2022) - Sun, Y.; Luo, M.; Zhao, S.; Shi, W.; Liu, Z.; Zhang, Q.; Guo, F.; Cai, W.; Sui, J.
Abstract: SnTe exhibits inferior thermoelectric performance because of the excess Sn vacancies, large energy offset between the two valence bands, and relatively high lattice thermal conductivity. Therefore, it is necessary to adopt a variety of means to optimize its thermoelectric performance synergistically. Here, the microstructure and thermoelectric properties for Sn0·99 In0·01 Te composited with CaMg2 Bi2 and YbMg2 Bi2 are reported. Ca (Yb) and Mg doping decreases the energy offset between the two valence bands, leading to an improved Seebeck coefficient. In addition, Bi and Sn phases gradually precipitate with the increase of alloying amount. The large number of phase interfaces and point defects scatter phonons strongly. Meanwhile, Mg volatilization produces lots of pores at grain boundaries, which play an important role in extending the phonon transmission path. These multiple effects lead to an ultralow lattice thermal conductivity. Consequently, peak ZT of 0.94 and 1.14 at 823 K are attained in Sn0·99 In0·01 Te-(CaMg2 Bi2 )0.025 and Sn0·99 In0·01 Te-(YbMg2 Bi2 )0.03, corresponding to average ZT (300–823 K) of 0.67 and 0.77, respectively. This work provides an ingenious way to realize extraordinary thermoelectric performance in SnTe. Graphical abstract: Image 1 Highlights: A series of Sn0·99 In0·01 Te–Ca(Yb)Mg2 Bi2 composites is prepared by hot pressing. Ca(Yb) and Mg doping enables band convergence and enhances Seebeck coefficient. Mg volatilization leads to multi-scale pores at the grain boundary. High ZT ave ∼0.77 from 300 K to 873 K is obtained in Sn0·99 In0·01 Te-(YbMg2 Bi2 )0.03 .